Nano-iron oxide accelerates growth, yield, and quality of Glycine max seed in water deficits - Dola, Dipanjoli Baral; Mannan, Md. Abdul; Sarker, Umakanta; Mamun, Md. Abdullah Al; Islam, Tofazzal; Ercisli, Sezai; Saleem, Muhammad Hamzah; Ali, Baber; Pop, Oana Lelia; Marc, Romina Alina (Frontiers in Plant Science, 2022)
Drought is one of the most destructive abiotic stresses that impact the growth, physiology, yield, and nutritional quality of seeds of crop plants. In modern agriculture, the use of nanoparticles can be beneficial due to their large surface area and higher potentiality to enter into the plant leaf during foliar application. This study aims to evaluate the effects of foliar spray of varying doses (0, 100, and 200 ppm) of the nano iron (Fe3O4) on the growth, physiology, yield, and seed nutritional quality of soybean under drought (40% of field capacity, FC) and well-watered (80% of FC) conditions. Leaf water status, chlorophyll content of leaves, the height of plant, leaf, stem, and petiole fresh weight, total dry weight, grain yield, protein, and oil content in soybean seeds suppressed by the applied drought stress. Under both drought (40% of FC) and controlled well-watered (80% of FC) conditions, the foliar application of nano iron substantially improved the growth, physiology, yield, and quality of soybean seeds. The nanoparticles at 200 ppm increased soybean seed yield by 40.12% and 32.60% in drought and well-watered conditions, respectively compared to the untreated plants. Furthermore, nano iron increased the oil contents of soybean seeds by 10.14% and 7.87% under drought and well-watered conditions, compared to the untreated control. Our results indicate that the application of nano iron improved drought tolerance, yield, and seed quality of soybean, so exogenous foliar sprays of 200 ppm Fe3O4 were more effective than the other treatments in enhancing drought tolerance and can be utilized to reduce losses caused by drought stress in soybean-growing areas.